Human cytomegalovirus infection, viraemia and retinitis among people living with HIV/AIDS in Kano, North-Western Nigeria - Edwin, Chinagozi P.; Hassan, Sadiq; Ebisike, Philips I.; Habib, Saudat G.; Amole, Taiwo G.; Bakare, Rasheed A. (International Journal of Research in Medical Sciences, 2021)
Background: Human cytomegalovirus (HCMV) is a leading cause of opportunistic infection in HIV-infected patients. HCMV viraemia is an active infection marker and prelude to end-organ diseases (EODs), such as retinitis. The aim of the study was to assess the burden and associated factors of HCMV infection, viraemia and retinitis among HIV-infected patients in Nigeria. Methods: Comparative cross-sectional study of 160 HIV-infected adults, comprising 80 participants in each of <100/mm3 and ≥100 cells/mm3 CD4+ cell count groups, who attended HIV clinic at a tertiary hospital located in a major Nigerian city. A questionnaire was used to collect data from eligible consenting participants and their case files. Sera from all participants were tested for anti-HCMV IgG using ELISA method, and plasma of seropositive participants were subjected to PCR for HCMV viraemia. Participants whose samples were HCMV viraemic were examined for HCMV retinitis using indirect ophthalmoscopy. Data was analyzed using Minitab vs 14.1.1PP. Results: All 160 participants tested positive for anti-HCMV IgG. HCMV viraemia was 14.4% (23 of 160) generally, but comparatively more among <100 CD4 cells/mm3 group (18.8%; 15 of 80) than in ≥100 cells/mm3 patient group (10%; 8 of 80). Only HCMV viraemic patients in <100 CD4 cells/mm3 group (20%; 3 of 15) were diagnosed with HCMV retinitis. WHO stage was associated with HCMV viraemia (χ2= 7.79, p=0.05) and HCMV retinitis (χ2= 4.60, p=0.03). The only predictor of HCMV retinitis was WHO staging I and II [aOR = 0.04, 95%CI (0.01- 0.52)]. Conclusions: Evidence of previous and active HCMV infection is prevalent among PLWHA in Nigeria with WHO staging being associated and a predictor of HCMV viraemia and retinitis, respectively.